1993
DOI: 10.1007/bf02600108
|View full text |Cite
|
Sign up to set email alerts
|

Management and prevention of thromboembolic events in patients with cancer-related hypercoagulable states

Abstract: Vena caval filter placement and long-term anticoagulation therapy yield similar outcomes in the setting of cancer-related hypercoagulable states. However, filter insertion is less expensive than anticoagulation. Given the short life expectancy and morbidity of patients with end-stage malignancy, patient preferences for health states must be considered in the decision-making process. If active treatment is pursued, vena caval filter should be used as a primary therapy. Prophylactic therapy is not warranted in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
7

Year Published

1997
1997
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(19 citation statements)
references
References 52 publications
0
12
0
7
Order By: Relevance
“…The published literature was used to identify utilities for PHN pain, relief from PHN pain, and the decrement in utilities from adverse effects [50][51][52][53][54][55] . Several studies were identified that measured health state utilities with neuropathic pain 9,14,51 .…”
Section: Methodsmentioning
confidence: 99%
“…The published literature was used to identify utilities for PHN pain, relief from PHN pain, and the decrement in utilities from adverse effects [50][51][52][53][54][55] . Several studies were identified that measured health state utilities with neuropathic pain 9,14,51 .…”
Section: Methodsmentioning
confidence: 99%
“…The hypercoagulability of malignancy, the presence of underlying inherited or acquired (e.g., antiphospholipid antibodies) hypercoagulable states, and exposure to situational risk factors (such as prolonged immobilization, surgery, central venous access devices, and chemotherapy itself) all can promote or trigger pathologic thrombosis. The impact of these risk factors on the overall risk of VTE can be illustrated by the fact that patients with breast carcinoma have an increased risk of VTE relative to patients of the same age but without cancer and have an even greater, exponentially increased VTE risk during chemotherapy (e.g., cyclophosphamide, methotrexate, and 5‐fluorouracil) 8, 9. The risks with newer chemotherapy regimens (e.g., doxorubicin and cyclophosphamide) and with sequential instead of concomitant chemotherapy plus hormone therapy may be different.…”
Section: Hormonal Agents Available or Under Study For The Prevention mentioning
confidence: 99%
“…We obtained utility values (Table 2) from previous publications and the Cost-Effectiveness Analysis Registry from the Institute for Clinical Research and Health Policy Studies, Tufts Medical Center [26-35]. We considered the baseline utility for our study (0.96) to be less than a perfect state of health (1.00) because all patients in our model would have already suffered a major trauma with associated head injury [36].…”
Section: Methodsmentioning
confidence: 99%